HUBUNGAN DUKUNGAN KELUARGA DENGAN PEMANFAATAN POSYANDU LANSIA DI DESA SIPANGKO - Lena Juliana Harahap (Jurnal Keperawatan Priority, 2021)
The existence of elderly posyandu is not balanced with the support of families to actively participate in the activities of elderly posyandu in Sipangko Village in 2020, out of 72 seniors who came to Posyandu in January as 19 people. The number is low when compared to the number of elderly. The indicates visits to Posyandu Lansia are still very low. This study aims to find the relationship of family support with the utilization of elderly posyandu in Sipangko Village, Angkola Muaratais District, South Tapanuli Regency in 2020. This type of research is an analytical survey with a cross-sectional approach, a population of elderly in sipangko village, Angkola Muaratais district, South Tapanuli Regency as many as 72 people. Sampling in this study was conducted in a total and analyzed using the Chi-Square test. The results showed a relationship of family support with the utilization of elderly Posyandu in Sipangko Village, Angkola Muaratais District, South Tapanuli Regency in 2020, with a value of p-value = 0.009 < 0.05. The expected that the Puskesmas include the role of elderly families in supporting the utilization of elderly posyandu. Provide understanding to family members forward elderly assistance is during posyandu and a sense of ownership to the elderly that posyandu belongs to the community so that indirectly the awareness of the elderly to utilize posyandu is increasing.